Complications of Parotid Surgery A Study of 30 Cases (Bangladesh Journal of Otorhinolaryngology, 2015)
Objectives: To find out the complication of parotid surgery and association of nerve injury with the type of disease pathology and type of parotid surgery.Methods: This cross-sectional study on 30 cases was carried out in the Department of Otolaryngology-Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University & Dhaka Medical College Hospital, Dhaka from September 2011 to September 2012. After taking history, clinical examination and investigation (FNAC, CT-scan) diagnosis was confirmed by histopathological examination.Results: In this study, lowest age was 14 years and highest age 65 years, male to female ration was 1.1:1. 83.33% cases were benign and 16.67% cases were malignant. Most of benign tumors was pleomorphic adenoma (80%). 88% cases involved in superficial lobe. Temporary facial nerve paresis was the most common postoperative complication (29.97%); 6.6% cases develoved permanent facial palsy and hypoesthesia of ear was 26.04%. Most patient regained normal facial nerve function within 6 months from the onset.Conclusion: Marginal mandibular nerve is the most common branch of facial nerve injury.Bangladesh J Otorhinolaryngol; April 2015; 21(1): 23-27